Eponyms in neuroanatomy: central nervous system - Svitlitsky , A.O.; Chernyavskiy , A.V.; Matvieishyna , T.M.; Shcherbakov , M.S.; Zinych, O.L. (Морфологія / Morphologia / Morfologìâ, 2023)
Despite the exclusion from the International Anatomical Nomenclature in 1955, eponymous names are still actively used in the work of specialists in various fields of medicine and scientists of theoretical disciplines. Anatomical terminology adopted by the International Federation of Anatomical Associations (IFAA), as well as in the International Neuroanatomical Terminology approved by IFAA in 2019. The purpose of this article was to update the study of the eponyms of the structures of the central nervous system (CNS) found in Ukrainian and foreign literature, as well as widely used by clinicians in their practice. The search and selection of literature for a systematic review was carried out by the authors independently in the PubMed, Scopus and Cochrane databases using the keywords "eponym", "anatomical terminology", "central nervous system", "neuroanatomy", in the full texts of articles in English and Ukrainian according to the results studies with evidence level I - III. The presented article complements the history of the formation of anatomical and medical terminology as a part of the research work initiated by a prominent Ukrainian scientist MD, PHD, DSc. M.A. Voloshyn. The intensive development of neuroscience in recent years has led to the need to revise anatomical nomenclature and even create a separate International Neuroanatomical Terminology, which preserves eponymous names. As a result of the research of current literary sources from more than 200 eponymous names from the anatomy of the central nervous system, 50 terms that are most often used in modern clinical neuroanatomy were selected. The terms are presented in the form of a systematic list, structured according to the parts of the brain and spinal cord. Brief information about scientists is also given, which is a personalized reflection of the history of the anatomical science development. In the future, it is planned to carry out a more detailed systematization of eponyms related to the peripheral nervous system and brain meninges.